2011
DOI: 10.9735/0975-3710.3.3.156-164
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Entomopathogenic Fungi From Lebanese Soils Against Aphids, Whitefly and Non-Target Beneficial Insects

Abstract: Three newly isolated and two existing isolates of M. anisopliae and B. bassiana were tested against aphids, whiteflies and beneficials, individually and with chitin synthesis inhibitor. Hundred percent of aphids have died of fungal treatments 7 days post inoculation, but number of individuals that developed mycosis varied depending on the isolate used. Whiteflies, however, were slightly more resistant. All tested isolates appeared to be fast killing fungi requiring only one or two days for reducing aphid popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In this study, the effects of metabolites and spore suspension of L. lecanii were investigated at different concentrations on some biological aspects of some developmental stages of the peach aphid (M. presicae), and the results obtained were similar to those obtained by Kim et al (2010) which revealed that degradation of insect body was observed in infiltrate treated aphids and the reduction of aphid population was more at high concentrations and high doses of filtrate treatments. Likewise, our results were in agreement with the results of Ibrahim et al (2011). In addition, our results were in agreement with those of Saranya et al (2010) who reported that L. lecanii, M. anisopliae and B. bassiana strains caused 100, 83.3 and 61.5% mortality, respectively, of cow pea aphid, Aphis craccivora after 7 days after treatment with a suspension of 10 7 spores/ml.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the effects of metabolites and spore suspension of L. lecanii were investigated at different concentrations on some biological aspects of some developmental stages of the peach aphid (M. presicae), and the results obtained were similar to those obtained by Kim et al (2010) which revealed that degradation of insect body was observed in infiltrate treated aphids and the reduction of aphid population was more at high concentrations and high doses of filtrate treatments. Likewise, our results were in agreement with the results of Ibrahim et al (2011). In addition, our results were in agreement with those of Saranya et al (2010) who reported that L. lecanii, M. anisopliae and B. bassiana strains caused 100, 83.3 and 61.5% mortality, respectively, of cow pea aphid, Aphis craccivora after 7 days after treatment with a suspension of 10 7 spores/ml.…”
Section: Discussionsupporting
confidence: 93%
“…El-Gendy (2015) found that the LC50 of biozed against B. brassicae was 55.8 ppm. Ibrahim et al (2011) found that the LC50 values were 103.88 and 104.75 conidia for the entomopathogenic fungi M. anisopliae and B. bassiana, respectively, against M. persicae. Moreover, Entesar et al (2020) reported that two isolates of B. bassiana (B1and B2) were evaluated against wheat aphid, Schizaphis graminum (Rondani), and the results showed that B1 isolate was the most effective.…”
Section: Discussionmentioning
confidence: 98%
“…Two strains, B. bassiana and M. anisopliae, isolated from fallow soil (Ibrahim et al 2011) were used in this study. Long term storage of the isolates was achieved by freezing conidia in 35% w/w glycerol at −80°C.…”
Section: Source Of Fungal Inoculummentioning
confidence: 99%